2021
DOI: 10.3390/biom11030452
|View full text |Cite
|
Sign up to set email alerts
|

The Ablation of VEGFR-1 Signaling Promotes Pressure Overload-Induced Cardiac Dysfunction and Sudden Death

Abstract: Molecular mechanisms involved in cardiac remodelling are not fully understood. To study the role of vascular endothelial growth factor receptor 1 (VEGFR-1) signaling in left ventricular hypertrophy (LVH) and heart failure, we used a mouse model lacking the intracellular VEGFR-1 tyrosine kinase domain (VEGFR-1 TK−/−) and induced pressure overload with angiotensin II infusion. Using echocardiography (ECG) and immunohistochemistry, we evaluated pathological changes in the heart during pressure overload and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Further, VEGFR2 expression was increased in TRPV4 ECKO hearts after TAC compared with TRPV4 lox/lox hearts, suggesting that increased VEGF/VEFR2 signaling may increase coronary angiogenesis in TRPV4 ECKO mice. Previous studies have shown that a lack of VEGFR signaling promotes pressure overload and angiotensin II-induced cardiac hypertrophy, 25,26 supporting a role for VEGF/VEGFR2 signaling in attenuating cardiac hypertrophy and pathological remodeling in TRPV4 ECKO mice. However, the molecular mechanism by which TRPV4 regulates VEGF/VEGFR2 signaling in the heart is not known.…”
Section: Discussionmentioning
confidence: 83%
“…Further, VEGFR2 expression was increased in TRPV4 ECKO hearts after TAC compared with TRPV4 lox/lox hearts, suggesting that increased VEGF/VEFR2 signaling may increase coronary angiogenesis in TRPV4 ECKO mice. Previous studies have shown that a lack of VEGFR signaling promotes pressure overload and angiotensin II-induced cardiac hypertrophy, 25,26 supporting a role for VEGF/VEGFR2 signaling in attenuating cardiac hypertrophy and pathological remodeling in TRPV4 ECKO mice. However, the molecular mechanism by which TRPV4 regulates VEGF/VEGFR2 signaling in the heart is not known.…”
Section: Discussionmentioning
confidence: 83%
“…VEGF-B-VEGFR1 mediated cardiac remodeling is crucial following myocardial infarction ( Devaux et al, 2012 ; Räsänen et al, 2021 ; Tirronen et al, 2021 ). We found that Ad-VEGF-B186R127S and Ad-VEGF-B186 induced angiogenesis in the heart muscle while not hampering cardiac performance.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, Korpela et al reported that the C-terminal fragment of the proteolytically spliced VEGF-B186 induced cardiac arrhythmias [ 45 ]. As VEGF-R1 is known to regulate cardiac performance [ 78 ], it is possible that due to the inability to bind to the VEGF-R1, the C-terminal end of the VEGF-B186 provokes arrhythmias via binding to an unidentified receptor in the heart.…”
Section: Cardioprotective Role Of Vegf-bmentioning
confidence: 99%